Could Sporadic Creutzfeldt-Jakob Disease Be Underdiagnosed in China? Experience From Four Cases - Zhang, Yi-Liu; Wu, Xiao-Mei; Chen, Yang; Gu, Wen-Ping; Lu, Wei (Frontiers in Neurology, 2020)
Background: Creutzfeldt-Jakob Disease (CJD) is a rapidly progressive neurodegenerative disease caused by the misfolded version of the cellular prion protein. Here we report four cases of sporadic CJD (sCJD) and describe the diagnostic methods available in order avoid missed or delayed recognition of CJD in China. Case presentation: We report four patients diagnosed with sCJD between March 2018 and December 2019 at Xiangya Hospital and the Second Xiangya Hospital of Central South University. All patients were admitted to the hospital because of a progressive cognitive decline. Although their routine tests and biochemical indicators in the cerebrospinal fluid (CSF), as well as computed tomography (CT) imaging, did not reveal any apparent abnormalities, the presence of “cortical ribboning” was incidentally found on diffusion-weighted imaging (DWI). The patients were subsequently diagnosed with CJD based on positive testing for 14-3-3 protein in their CSF, and the presence of periodic sharp and slow wave complexes (PSWCs) on their electroencephalograms (EEG). Additionally, two of patients was confirmed pathological examination of cerebral biopsies demonstrating neuronal loss, gliosis and spongiform changes. Conclusions: CJD is a rare disease and is easily misdiagnosed by clinician in China due to a lack of recognition and awareness of CJD. Based on our experience described in this report, enhanced vigilance for CJD is required for patients with rapidly progressive dementia in China and other developing countries. DWI, EEG and detection of 14-3-3 protein in CSF should be performed in order to achieve a timely diagnosis of CJD.